PENGARUH DIGITALMARKETING DAN PERCEIVEDQUALITY TERHADAP KEPUASAN PELANGGAN BARBERSHOP YANTO KOTA BENGKULU - Frengky Mellyan Frendes; Subandrio Subandrio (UM. Bengkulu, 2023)
This study aims to determine the effect of Digital Marketing and Perceived Quality on Customer Satisfaction at Yanto's Barbershop, Bengkulu City. The results of this study indicate that partially the Digital Marketing variable has a significant effect on the Customer Satisfaction variable, H1 is accepted and Perceived Quality has a significant effect on the Customer Satisfaction variable, H2 is accepted. While the Digital Marketing f Test(X1) and Perceived Quality(X2) have a significant influence on Customer Satisfaction(Y) Barbershop Yanto Bengkulu City so that H3 is accepted. The overall significant level is (sig Î±=0.000<0.05. The coefficient of determination(R2) for the value of R Square is 0.380. Where the coefficient of determination means that together digital marketing and perceived quality make a major contribution in influencing Customer Satisfaction at Barbershop Yanto, Bengkulu City. The most dominant factor with the largest regression coefficient value is the variable Perceived Quality(X2) with a value of 0.279. Keyword: Digital Marketing and Perceived Quality on Customer Satisfaction